Fractions of soil organic matter in the vineyards of altitude regions in Santa Catarina - Denilson Dortzbach; Shirlei Almeida Assunção; Marcos Gervasio Pereira; Eduardo Carvalho da Silva Neto (Semina: Ciências Agrárias, 2017)
The implementation of agricultural systems such as viticulture can quantitatively and qualitatively affect the contents of soil organic matter (SOM). These changes may modify the edaphic features of the soil as well as the soil quality. The objective of this study was to evaluate the chemical and physical fraction of SOMand to analyze changes in the carbon stock and C management index in areas of implanted vineyards in altitude regions of Santa Catarina. Four regions were selected: Region I (Urubici); Region II (San Joaquim); Region III (Campos Novos) and Region IV (Água Doce). In each region, we selected vineyards implanted between 2001 and 2005 as well as surrounding forested areas. Disturbed and undisturbed samples were collected from the 0-5, 5-10, and 10-20 cm layers of the soil. Samples were prepared in the laboratory to obtain air-dried soft soil, which was then used for the analysis of several parameters, namely total organic carbon (TOC), carbon stock,and chemical fractionation of the soil. The chemical fractionation was then used to determine carbon content in the fulvic acid fraction (C-FAF), humic acid fraction (C-HAF), and humin fraction (C-HUM). We also analyzed particle size, quantified the levels of particulate carbon (COp) and carbon associated with clay and silt (COam), and calculated the carbon management index (CMI). We evaluated normality and homogeneity for all data. The results were evaluated with an analysis of variance and subsequent F-test. Mean values were compared using a 5% Student’s t-test and subsequently submitted to a Tukey’s test. The highest TOC levels were observed in Region II in the 0-5 cm layer in both vineyard and forested areas. Vineyard areas exhibited lower values of TOC, Cop, and COam compared to forested areas indicating that the management adopted in these areas contributed to the reduction of these fractions. Forested areas exhibited a higher proportion of Cop compared to vineyard areas. The humin fraction represented the largest portion of the TOC and comprised the highest values in both forested and vineyard areas. The carbon management index indicated a low contribution of vineyard areas or a reduction in carbon storage in their soils.